(untitled) (Mongolian Journal of Agricultural Sciences, 2024)
In this investigation, the microstructure changes of 0.25% low carbon steel, which is hardfaced with high chromium white iron by a semiautomatic welding process was studied using OM, SEM and EDX analysis. Mechanical properties, such as hardness and wear rates, were also investigated. Four groups of samples were used in the study. The first group of samples was low carbon steel without any surface treatment. The second, third, and fourth groups of samples were selected from several hard-faced low carbon steel pieces with 3.0, 3.4 and 3.8 % of chromium contents in their hard-faced surface respectively. SEM analysis results show that the microstructure of the surface treated samples consist of a small amount of ferrite and a large amount of pearlite. EDS test shows that the chromium contents of both ferrite and pearlite have increased significantly. Increasing pearlite amounts and increasing chromium concentrations in every phase seem to increase the hardness from 280 to 495 HV30. Chromium content was increased in both pearlite and ferrite. This increase causes the phase’s hardness to be increased. Also, there is a trace of М7С type carbides that appeared in hardfaced surface with higher chromium content.